Demystifying bioethics: The past, present, and future of a flourishing discipline - Ruaim A Muaygil (Wolters Kluwer Medknow Publications, 2020)
Despite interest in bioethics being arguably at its highest, the history, development, and tasks of this practice remain elusive to many medical practitioners. This ambiguity is not without good reason; unlike its clinical counterparts, bioethics is not exclusively a child of medicine. Rather, bioethics also belongs to theology, philosophy, sociology, and the law. Its intellectual assumptions are multi-disciplinary and wide-reaching, in contrast to those of medicine-neatly delineated and perfected by the scientific method. Indeed, bioethics is contemplative where medicine is active, inquisitive where medicine is decisive, and measured where medicine is efficient. Although at first glance, bioethics may not appear to share much with medicine, the discipline has become an essential conduit of moral medical practice. This manuscript gives an account of the history and development of contemporary bioethics in both the Islamic and Western world, its current state of affairs, its tasks, and its future. Ultimately, it is hoped that this work will demystify the practice of bioethics and elucidate the role of the bioethicist as a partner to the practitioner, an ally to the patient, and an advocate for the moral practice of medicine.